Feasibility, Safety, and Efficacy of Flow-Diverting Stent-Assisted Microsphere Embolization of Fusiform and Sidewall Aneurysms. Issue 1 (14th February 2015) - Nonn, Andrea; Kirschner, Stefanie; Figueiredo, Giovanna; Kramer, Martin; Nikoubashman, Omid; Pjontek, Rastislav; Wiesmann, Martin; Brockmann, Marc A.
Abstract: BACKGROUND: Treatment of wide-necked internal carotid artery aneurysms is frequently associated with incomplete occlusion and high recurrence rates. Furthermore, platinum coils cause strong beam-hardening artifacts, hampering subsequent image analyses. OBJECTIVE: To assess the feasibility, safety, and efficacy of flow-diverting, stent-assisted microsphere embolization of fusiform and sidewall aneurysms in vitro and in vivo. METHODS: Using a recirculating pulsatile in vitro flow model, 5 different aneurysm geometries (inner/outer curve, narrow/wide neck, and fusiform) were treated (each n = 1) by flow-diverting stent (FDS) implantation and subsequent embolization through a jailed microcatheter using calibrated microspheres (500–900 μm) larger than the pores of the FDS mesh. Treatment effects were analyzed angiographically and by micro computed tomography. The fluid of the in vitro model was filtered to ensure that no microspheres evaded the aneurysm. The experiment was repeated once in vivo. RESULTS: In vitro, all 5 aneurysms were safely and completely occluded by FDS-assisted microsphere embolization. Virtually complete aneurysm occlusion was confirmed by angiography and micro computed tomography. No microspheres escaped into the circulation. The experiment was successfully repeated in 1 pig with a sidewall aneurysm generated by vessel occlusion. An embolic protection system placed distally of the FDS in vitro and in vivo (each n = 1) contained no microspheres after the embolization. Thus, no microspheres were lost in the circulation, and the use of an embolic protection system seems feasible to provide additional safety. CONCLUSION: FDS-assisted microsphere embolization of fusiform and sidewall aneurysms is feasible and yields virtually complete aneurysm occlusion while avoiding coil-associated beam-hardening artifacts.